Pengaruh Burnout dan Work Life Balance terhadap Kinerja Pegawai Inspektorat Provinsi Bengkulu - Rahmadani, Muhammad Genta; Puspita, Veny; Waliamin, Janusi (Jurnal Manajemen Bisnis dan Keuangan, 2023)
Burnout is a form of work-related stress that has the potential to negatively affect an individual's psychological and physical health. The purpose of this study was to determine how much influence burnout and work-life balance have on the performance of the Bengkulu Provincial Inspectorate employees. The variables of this study are burnout and work-life balance. The method used in this research is distributing questionnaires. This research is a quantitative approach research. The research population was all employees of the Bengkulu Provincial Inspectorate, with 123 samples with the saturated sample method. The analytical tool used in this study uses SPSS 22. The data analysis method used is multiple linear regression. The results showed that burnout had no significant effect on the performance of the Bengkulu Provincial Inspectorate employees, a work-life balance had a significant effect on the Bengkulu Province Inspectorate employee performance, and burnout and work-life balance simultaneously affected the Bengkulu Province Inspectorate employee performance.